Science e-Module Based on Scientific Approach Using Kvisoft Flipbook on Temperature and Heat Materials in Class VII Junior High School - Alya Armani; M. Rahmad; Zulhelmi Zulhelmi (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2021)
The era of the industrial revolution 4.0 requires a teacher must be able to keep up with the era to create interesting learning and easy for students to understand. In addition, the Covid-19 pandemic requires virtual learning from home. We need a learning resources, one of which is e-modules in the learning process. This research purpose to develop student learning resources in the form of an e-module temperature and heat based on a scientific approach by the Kvisoft Flipbook in e-learning. This research uses the type of R&D (Research and Development) with the ADDIE model which only applies 4 steps, there are analysis, design, development, and evaluation steps. The data required is in the form of quantitative data, namely 1) questionnaire respondent data about the need for learning resources that are distributed to students, and 2) data on the e-module validation assessment score by the validator. Research instruments used were questionnaires and e-module validation sheets. Data were analyzed descriptively to determine the validity of the e-module. The results showed that the average score for the validation of the entire e-module was declared valid based on aspects of content, presentation, language, and graphics with a high category of 3.46. Thus the science e-module based on a scientific approach using the kvisoft flipbook on temperature and heat material has been successfully developed with valid criteria and is suitable for use as a learning resource in online science learning in Class VII junior high school.